Different types of international new ventures: A latent class analysis - Baum, M; Schwens, C; Kabst, Rüdiger

The different types of international new ventures: A latent class analysis - Baum, M; Schwens, C; Kabst, Rüdiger

The impact of employer awards on employer knowledge and applicant attraction: The moderating influence of corporate brand awareness - Baum, M; Kabst, Rüdiger

,,Blended Professionals´´ als Akteure einer institutionsweiten Hochschulentwicklung - Jenert, Tobias; Brahm, Taiga (Zeitschrift für Hochschulentwicklung)
Die aktuelle hochschuldidaktische Diskussion ist durch Schlüsselbegriffe wie Outcome- und Kompetenzorientierung geprägt. Allerdings sind die Strategien zur nachhaltigen Gestaltung der Lehr- und Lernpraxis bisher nur wenig differenziert. Der Beitrag stellt das Konzept einer "institutionsweiten Hochschulentwicklung" vor. Dieses spricht individuelles Handeln von Lehrenden und Lernenden sowie curriculare und organisationale Aspekte an. Mittels Experteninterviews wird gezeigt, dass Hochschulentwicklung eine "Third-Space-Funktion" zwischen Akademie und Administration einnimmt. Das personelle Profil solcher Einrichtungen verlangt nach "Blended Professionals", die sowohl als Servicepersonal als auch als Mitglieder der akademischen Welt wirkungsvoll agieren können.
Keywords: Hochschulentwicklung; educational development; higher education; Hochschuldidaktik

Zugänge zum Begriff der Lernkultur: Eine Systematisierung auf Basis kultur-und lerntheoretischer Überlegungen - Jenert, Tobias; Gebhardt, Anja
"Lernkultur" wird als Begriff häufig gebraucht und fast ebenso häufig definiert  das gilt für den betrieblichen Kontext ebenso wie für die Bereiche der Schul-, Hochschul-, Berufs- und Erwachsenenbildung (z. B. Wulf, Althans, Blaschke, Ferrin, Göhlich, Jörissen, Mattig et al., 2007; Jenert, Zellweger Moser, Dommen & Gebhardt, 2009; Kirchhöfer, 2004; Erpenbeck & Sauer, 2000). Trotz der grossen Aufmerksamkeit, die der Begriff in den letzten zwei Jahrzehnten erfahren hat, kann man nicht von einem in sich geschlossenen Forschungsprogramm sprechen. Die Zugänge zum Phänomenbereich Lernkultur sind ebenso vielfältig wie die hinter einzelnen Ansätzen stehenden Lernkulturkonstrukte. Den Autoren ist keine Publikation bekannt, welche unterschiedliche Ansätze der Lernkulturforschung systematisch aufarbeitet. Eine wichtige Referenzquelle ist der Bericht von Kuh und Whitt (1988) "The Invisible Tapestry: Culture in American Colleges and Universities". Ausgehend von einer fundierten Übersicht zu unterschiedlichen Zugängen zum Kulturbegriff (oft in starker Anlehnung an die Organisationskulturforschung (vgl. Allaire & Firsirotu, 1984)) stellen die Autoren ein Rahmenmodell zur Analyse von Hochschulkulturen vor (Kuh und Whitt, 1988, S. 56). Diese Arbeit erweist sich für ein besseres Verständnis unter-schiedlicher Zugänge zum Lernkulturbegriff als aufschlussreich, weil im Kontext Hoch-schule zwangsweise viele Aspekte des Lernens und Lehrens angesprochen werden. Allerdings fokussiert auch dieser Bericht nicht das Konstrukt der Lernkultur und bietet damit nur einen Ausgangspunkt für die Identifizierung unterschiedlicher Zugänge.
Keywords: Lernkultur; learning culture; culture theory; approaches to learning culture; culture of learning

Hochschulentwicklung als Gestaltung von Lehr-und Lernkultur: eine institutionsweite Herangehensweise an lehrbezogene Veränderungsprojekte an Hochschulen - Brahm, Taiga; Jenert, Tobias; Meier, Christoph
Keywords: Lernkultur; Hochschulentwickung; Hochschuldidaktik; Hochschullehre; HEI development

Learning Cultures at Higher Education Institutions: Outlining a wohle-institution approach to teaching and learning - Jenert, Tobias; Gebhardt, Anja
Keywords: earning culture; Lernkultur; whole-institution approach; higher education; Hochschule

Cultural Explorations: How Socio-material Contexts Influence Knowledge Interaction - Jenert, Tobias (Beyond Knowledge Management)

Oxygen sensing by fluorescence quenching of [Cu(btmgp)I] - Herres-Pawlis, Sonja; Berth, Gerhard; Wiedemeier, Volker; Schmidt, Ludger; Zrenner, Artur; Warnecke, Hans-Joachim (Journal of Luminescence)
A fluorescence study of acetonitrile solutions of bis(tetramethylguanidine)propane, copper(I)-iodide and [Cu(btmgp)I] was performed and the chemical reaction of the latter species with O2 was investigated at room temperature. The actual quenching process via O2 gassing was studied and an exponential dependence of the fluorescence intensity with respect to the complex concentration was observed. Furthermore the survey was deepened on time resolved fluorescence properties of solved [Cu(btmgp)I] in a wider concentration range. The applicability of this complex for O2 sensing inside a microreactor system was proven by confocal fluorescence measurements. It was shown that the investigated system can be used for oxygen sensing in the copper concentration range from 10−2 to 10−9 mol/l.
Keywords: Copper Oxygen Fluorescence quenching N donor ligands

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

An intentionally positioned (In,Ga)As quantum dot in a micron sized light emitting diode - Mehta, M.; Reuter, Dirk; Wieck, A. D.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Meier, Cedrik (Applied Physics Letters)
We have integrated individual (In,Ga)As quantum dots (QDs) using site-controlled molecular beam epitaxial growth into the intrinsic region of a p-i-n junction diode. This is achieved using an in situ combination of focused ion beam prepatterning, annealing, and overgrowth, resulting in arrays of individually electrically addressable (In,Ga)As QDs with full control on the lateral position. Using microelectroluminescence spectroscopy we demonstrate that these QDs have the same optical quality as optically pumped Stranski–Krastanov QDs with random nucleation located in proximity to a doped interface. The results suggest that this technique is scalable and highly interesting for different applications in quantum devices.

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Resonant photocurrent-spectroscopy of individual CdSe quantum dots - Panfilova, M.; Michaelis de Vasconcellos, S.; Pawlis, A.; Lischka, K.; Zrenner, Artur (Physica E: Low-dimensional Systems and Nanostructures)
Here we report on investigations on CdSe quantum dots incorporated in ZnSe based Schottky photodiodes with near-field shadow masks. Photoluminescence and photocurrent of individual quantum dots were studied as a function of the applied bias voltage. The exciton energy of the quantum dot ground state transition was shifted to the excitation energy by using the Stark effect tuning via an external bias voltage. Under the condition of resonance with the laser excitation energy we observed a resonant photocurrent signal due to the tunnelling of carriers out of the quantum dots at electric fields above 500 kV/cm.
Keywords: CdSe/ZnSe quantum dots; Photodiode; Quantum confined Stark Effect; Photocurrent; II–VI Semiconductors

An empirical examination of the contribution of capabilities to the competitiveness of logistics service providers - Liu, Xiaohong; Grant, David B.; McKinnon, Alan C.; Feng, Yuanhua (International Journal of Physical Distribution & Logistics Management)

Sources of competitiveness for logistics service providers: a UK industry perspective - Liu, Xiaohong; McKinnon, Alan C.; Grant, David B.; Feng, Yuanhua (Logistics Research)

Managing customer share in key supplier relationships - Eggert, Andreas; Ulaga, Wolfgang (Industrial Marketing Management)

Creating and appropriating value in collaborative relationships - Wagner, Stephan M; Eggert, Andreas; Lindemann, Eckhard (Journal of business research)

Kundenbindung auf Basis des Relationship Value - Eggert, Andreas; Garnefeld, Ina (Handbuch Kundenbindungsmanagement)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Individuelle Förderung in der beruflichen Bildung. Grundlegung und Annäherung im Kontext von Forschungs- und Entwicklungsprojekten